Electroosmotic Dewatering of Iron Ore Tailings: A Laboratory Study to Improve Geotechnical Properties - Salih Yüksek (Advances in Civil Engineering)
Minerals are subjected to ore processing to turn them into usable and saleable raw materials. First of all, the ore is reduced to the smallest size with the crushing-grinding process, and after using water and chemical additives, according to the characteristics of the ore, useful minerals are taken, and unwanted minerals are stored in the tailings pools. Approximately, 26 million tons of mineral wastes were generated annually from ore processing facilities in Turkey. The construction of tailings pools, the stability of the tailing sludge, and the safety of dams are a burdensome issue faced by miners. In the ore plants, an average of 3 tons of water is used to enrich 1 ton of ore, and most of the wastewater cannot be removed by traditional methods, causing various economic, environmental, and stability problems. In this study, the dewatering of an iron ore tailing by applying different voltages by the electroosmosis method was investigated in the laboratory environment. By discharging the water of the iron ore tailings by the electroosmosis method, the solid content was increased from 43.01% to 87.63%. Thus, it has been observed that there will be a significant improvement in the geotechnical properties of the tailings’ material. It has been estimated that electroosmotic dewatering rises with increasing the voltage gradient and the energy consumption varies in the range of 0.588–30.645 kWh/dry ton. The void ratio decreased from 5.58% to 0.23%. In the dewatering experiments, different parameters such as the amount of water discharged, density, void ratio, water content, and power consumed were measured or calculated and the relationships between them were discussed with graphics. In electroosmosis experiments, it has been observed that besides the voltage applied in the discharge of water, the mineralogy of the tailings has a significant effect. Since there are serious abrasions on the electrodes used in the experiments, alternative electrodes should be tried.